Value Relevance of Accounting Numbers: Evidence from The Jakarta Stock Exchange (Jsx) - Eko Suwardi (Jurnal Akuntansi dan Auditing Indonesia, 2005)
This paper investigates value relevance of accounting numbers of the firms listed at the Jakarta Stock Exchange (JSX) for the period of 1993-2001. This study reveals that combined value relevance of both book value and residual earnings in-creased steadily from 1993 until 2001, except for the crisis year in 1998. When in-vestigated separately, the value relevance of book value increased dramatically from 1993 to 2001, but decreased slightly in the crisis year 1998. On the other hand, the value relevance of residual earnings decreased significantly from 1993 to 1999 and increased to the highest level in 2000. Consistent with these findings, the incre-mental value relevance of book value increased with the highest level in 1997, whereas the incremental value relevance of residual earnings decreased from 1993 to the zero in 1996 until 2001.Keywords: Value relevance, accounting numbers, and JSX.